Fibrinolytic Shutdown Is Associated With Intraoperative Thrombosis and Hemorrhage During Visceral Transplant. (September 2019) - Raveh, Yehuda; Souki, Fouad; Livingstone, Joshua; Beduschi, Thiago; Vianna, Rodrigo; Rodriguez, Yiliam; Nicolau-Raducu, Ramona
Background and Objective . End-stage liver disease is characterized by a precarious imbalance of hemostasis. Detrimental consequences of hypofibrinolysis, also known as fibrinolytic shutdown, have been recently demonstrated, and its significance in visceral (ie, an allograft that contains the intestine) transplant remains unknown. Design and Setting . To fill this gap, following institutional review board approval, this retrospective study included 49 adult recipients of visceral allografts (14 "visceral allograft without the liver" and 35 "multivisceral" with the liver) transplanted between 2010 and 2018 in a single university hospital, and for whom pre-incisional thromboelastography was available. Based on percent clot lysis 30 minutes after maximal amplitude, patients were stratified into 3 fibrinolysis phenotypes: fibrinolytic shutdown, physiologic fibrinolysis, and hyperfibrinolysis. Results . Fibrinolytic shutdown occurred in 57% of patients, with higher incidence in recipients of multivisceral transplant (69%) compared with visceral allograft without liver (29%) allografts ( P = .04). Fibrinolytic shutdown was associated with an increase in both intraoperative thrombosis and hemorrhage. Intraoperative thrombosis (18%) occurred only with multivisceral transplant, and accounted for 36% of in-hospital mortality. A clinically meaningful reduction in incidence of intraoperative thrombosis was noted in recipients who received intravenous heparin thromboprophylaxis. Logistic regression identified pretransplant platelet count as a risk factor for fibrinolytic shutdown (odds ratio = 0.992, 95% confidence interval = [0.984-0.998]; χ 2 = 7.8, P = .005). Conclusions . This study highlights fibrinolytic shutdown as a dominant and clinically important feature of the hemostatic imbalance in recipients undergoing visceral transplantation.